Molecular and biological markers for assessing endometrial receptivity in infertile women: A narrative review - Junfeng Li; Hange Liu; Justin Lim; Hang Xing; Yuan Chen; Shaozhe Yang; Xiuhong Fu (Journal of International Medical Research)
Successful embryo implantation relies on embryo quality, endometrial receptivity, and the synchronized development of both. In recent years, methods for assessing endometrial receptivity have considerably advanced, shifting from traditional imaging techniques to modern molecular biology approaches. The evaluation of endometrial thickness, morphology, subendometrial blood flow, and peristalsis before implantation has become less prominent, whereas molecular markers such as pinopodes, integrin αvβ3, its ligand osteopontin, and homologous box gene A10 are widely used in clinical practice for assessing endometrial receptivity. To provide a comprehensive overview, this narrative review systematically searched PubMed and Web of Science for studies on endometrial receptivity assessment in infertile women over the past two decades, with a focus on both clinical and experimental research. This narrative review has examined recent advancements in morphological markers, endometrial receptivity–related genes, endometrial microbiota, and other emerging indicators, emphasizing their potential in optimizing embryo implantation and improving the success rates of assisted reproductive technologies. Notably, endometrial receptivity array testing and uterine microbiome analysis have gained substantial attention for their potential in personalized diagnosis and treatment. This review aims to provide scientific insights for precise infertility diagnostics and individualized treatment strategies while offering recommendations for future research development.